2020
DOI: 10.1039/d0md00145g
|View full text |Cite
|
Sign up to set email alerts
|

Natural product inspired optimization of a selective TRPV6 calcium channel inhibitor

Abstract: Natural product derived analogues were surveyed, and an oxygenated analog was identified as a potent and selective TRPV6 inhibitor, with high microsomal stability and low off-target effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…S7C). We also tested the effect on Cd 2+ influx of the recently synthesized PCHPDs inhibitor 3OG, which is among the most promising inhibitors in this class (23). We found that 1 M 3OG showed no inhibition of Cd 2+ influx through D580N mutant channels, while it inhibited nearly 70% of Cd 2+ influx through wild-type hTRPV6 channels ( fig.…”
Section: Functional Evaluation Of the Pchpd Pore Binding Sitementioning
confidence: 97%
See 1 more Smart Citation
“…S7C). We also tested the effect on Cd 2+ influx of the recently synthesized PCHPDs inhibitor 3OG, which is among the most promising inhibitors in this class (23). We found that 1 M 3OG showed no inhibition of Cd 2+ influx through D580N mutant channels, while it inhibited nearly 70% of Cd 2+ influx through wild-type hTRPV6 channels ( fig.…”
Section: Functional Evaluation Of the Pchpd Pore Binding Sitementioning
confidence: 97%
“…Several small-molecule inhibitors of TRPV6, including 2-aminoethoxydiphenyl borate (2-APB; IC 50 = 71 M), have been identified, but the majority either are nonspecific or have low potency (17)(18)(19)(20)(21). In contrast, we developed the first small-molecule TRPV6 inhibitors, (4-phenylcyclohexyl)piperazine derivatives (PCHPDs), that are highly selective and have nanomolar affinity (21)(22)(23). Here, we solve x-ray and cryo-electron microscopy (cryo-EM) structures of TRPV6 in complex with several PCHPD inhibitors and identify PCHPD binding sites in the channel's TM domain.…”
Section: Introductionmentioning
confidence: 99%
“… [35] Some of these molecules have displayed biological activity. For example, penindolones were found to inhibit membrane fusion of the Influenza A virus, [42] and derivatives of piperazopyridones were identified as TRPV6 channel inhibitors [75] . Other applications include the preparation of pseudo‐NP dyes from betelamic acid [76] .…”
Section: Discussionmentioning
confidence: 99%
“…Chow et al (2007) [ 209 ] suggested that 77 induces apoptosis preferentially via TRPV6, with selectivity for tumor cells. Recently, however, the activity of 77 against TRPV6 was evaluated in a Ca 2+ flux assay [ 134 , 210 ]. The authors observed that in this assay, the compound was not able to change the channel transport.…”
Section: Literature-related Cytotoxic Compoundsmentioning
confidence: 99%
“…In vivo mice models revealed that administration of 77 significantly reduced tumor growth (>50%) in breast and leukemia cancers [ 76 , 213 ]. As the inherent pungency of 77 greatly limits its application in therapeutics, it has led several research groups to design analogues lacking pungency of 77 [ 129 , 131 , 132 , 133 , 210 , 214 , 215 ].…”
Section: Literature-related Cytotoxic Compoundsmentioning
confidence: 99%